Prevalence, pattern and attitude towards self-medication practice for dental problems in Kuantan, Pahang - Mohd Haron, Muhammad Nabil; Abdul Majid, Muhammad Nazmi; Ismail, Azlini; Abllah, Zurainie (2020)
Introduction: Self-medication is a common practice worldwide, but there is no self-medication study focusing on dental problems in Malaysia. Aims and objectives: This study aims to determine prevalence, pattern and attitude of self-medication practice for dental problems among adults in Kuantan, Pahang as well as to study association of this practice with socio-demographic factors. Materials and methods: This cross-sectional study was conducted among adults aged 18 years old and above who lives in Kuantan, Pahang. The questionnaire set was constructed, face-to-face validated and was checked for reliability during pilot study on 54 respondents. Main study using web-based and paper-based questionnaire gathered 275 respondents. Descriptive statistics and chi-square test was run using SPSS software. Results: Majority of respondents were Malay (97.5%), aged 18 to 27 year-old (82.2%), lived in urban area (70.5%) and were graduates with at least Diploma level (73.1%). Only one-fifth of respondents (21.8%) practiced self-medication for dental problems. They gained information regarding \self-medication for dental problems mainly from internet (62%) and obtained the medication from pharmacy (78%). The common cause for self-medication is toothache (76%) and majority of them used paracetamol (62%) for relief. The main cause to self-medicate was due to mildness of illness (60%). Respondents have negative attitude towards self-medication practice for dental problems. There was significant association between this practice with gender, X2 (1, N = 275) = 4.916, p< 0.05. Conclusion: Prevalence of self-medication practice for dental problems among adults in Kuantan is considerably low and they have negative attitude towards this practice.